Recidivism among juvenile delinquents: Self-reported sociodemografic characteristics, behavioural features and perceptions of delinquency - Stavros P. Kiriakidis (Ψυχολογία: το Περιοδικό της Ελληνικής Ψυχολογικής Εταιρείας, 2020)
THE ABSTRACT IS AVAILABLE IN THE PDF